Asmaball is an alternative sport games for asthmatics of senior high school - Antonius Tri Wibowo; B.M. Wara Kushartanti; Dody Tri Iwandana (Nicolaus Copernicus University in Toruń, 2020)
The main aims of this study are to create a modified soccer games for Atsmatic highschool  students. The modified game hopefully can be an alternative way for sport teacher to teach soccer for Asthmatic students and make the student interested in playing it. This study was research and development type by adapting Borg & Gall's (1983: 775) procedur of R&D research as follows: (1) data collection, (2) data analysis, (3) first draft product development, (4) expert validation and revision, (5) small scale product testing and revision, (6) large scale product testing and revision, and (7) final product development. Small scale product testing was done in Kolese Debritto Highschool, with 26 asthmatic students, class X and XI. The results of the study is a modul of modified soccer for asthmatic Highschool Students. From the expert judgement, it can be seen that the modified soccer game is good and effective for atsmatic students who want to play soccer and can be used as theraphy. The modified game can be an alternative way for sport teacher to teach soccer for asthmatic students and make the student interested in playing it. Keywords: Soccer, Asthma